Electromagnetic actuated CVT system for vehicle - Rahman, Mohammed Ataur; Mohiuddin, A. K. M. (2009)
Electromagnetic Actuated Continuously Variable Transmission (CVT) system offers an opportunity to meet the challenge due to its improving automotive drivability and better fuel economy and dramatically reducing greenhouse gas emissions. The pushing and pulling the sheaves of the pulleys are conducted in this study in order to maintain the desired transmission ratio or gear ratio of the passenger car in all types of the road by developing electromagnetic solenoids (electromagnetic actuators). The operation of the solenoid is performed by controlling the eddy current with the aids of the lead acid battery, magnetic pick-up sensor and potentiometer. The response of the electromagnetic actuator is so fast that it can move both the sheaves of pulley at desired distance within fraction of seconds (0.01 s) in order to maintain the desired torque to the driving wheels in any road condition. The ability of the actuator is examined by applying additional load, voltage and number of turns of the solenoid. Experimentally, it was found that the EMA-CVT system was able to improve the 60% transmission losses of the car.